Identification of potential non-timber uses in remaining Araucaria Forest, Bituruna – Paraná (Research, Society and Development, 2022)
The objective of the study was to characterize the potential of non-timber uses of forest species present in the remnants of three municipal natural parks, in Bituruna, Paraná. For data collection, plots were installed in each of the parks. Each plot was defined by a sampling line of 25 meters, with a width of 2 meters on each side of the line, totaling 4 meters in width. The floristic survey was carried out using the guidance method, obtaining samples of tree and shrub species with a height equal to or greater than 50 cm, measured from the base of the soil. Botanical material was collected and the samples were labeled for identification in a herbarium. Subsequently, the identified species were classified into use categories, according to the consulted bibliography. The categories defined were: food, artisanal, ecological, fiber, medicinal, biochemical products, essential oils, ornamental and other uses. The study identified the occurrence of 141 species belonging to 39 botanical families, and 102 species were identified related to the use categories identified by the study. The families with the highest number of species for non-timber uses were: Myrtaceae (17), Asteraceae (11) and Lauraceae (7). The categories with the highest number of species were: medicinal (54), ecological (46), ornamental (43), essential oils (24), food (21) and biochemical products (17). The other categories presented values ​​lower than 10 species. In the study site, there are a significant number of species with potential for non-timber use, many are not properly researched and commercialized.